External risk factors associated with language disorders in children - Lydia Wangke; Wenny Victory; Gregory Joey; Novie Homenta Rampengan; Hesti Lestari (Indonesian Pediatric Society, 2021)
Background Children with language delay have deficits in the ability to learn and use language, either expressive and/or receptive despite otherwise normal development. Language delay could be influenced by either internal factors (within the child) and external factors (from the environment). Timely identification and modification of these risk factors can allow early intervention to reduce child disability and are associated with better long-term outcomes. Objective To identify possible risk factors related to language delay in children, such as bilingualism, socioeconomic status, maternal and caregiver education level, use of digital media, absence of story reading sessions, breastfeeding patterns, siblings, parenting methods, and maternal occupation. Methods This observational, analytic study included 102 children aged 24-36 months from four daycare centers in Manado, North Sulawesi, selected by cluster random sampling. Parents were interviewed to gather demographic information of child age, gender, presence of older siblings, maternal occupation, socioeconomic status, maternal/caregiver educational level, use of digital media, absence of story reading sessions, breastfeeding patterns, parenting methods, and bilingual environment. Children’s language development was assessed by the Capute Scales. Results Multivariate analysis revealed 2 factors significantly associated with increased risk of language delay; namely absence of storybook reading (OR=0.16; 95%CI 0.03 to 0.72; P=0.017) and bilingualism (OR=12.58; 95%CI 1.57 to 100.81; P=0.017). Conclusion Story reading sessions is associated with decreased risk of language delay, shile bilingualism is associatd with increased risk of language delay.